Revestimento a base de albumina sobre as características microbiológicas e de qualidade de ovos brancos de poedeiras comerciais - AMANDA ALICE LAPA SANTOS (2024)
Egg quality is defined as the set of external and internal characteristics that influence the accessibility of the product on the market, it is directly linked to the characteristics of the layer, such as lineage, age, nutritional and health condition, among other factors. Quality loss is slow and continuous, and can be accelerated by several environmental factors. Therefore, the study was carried out with the objective of evaluating coatings based on albumin and albumin + glycerol on the shell of white eggs, with or without exposure to ultraviolet light (UV) and stored for different periods at room temperature (25ºC). Microbiological analyzes were carried out to identify Salmonella and select E.coli colony-forming units and determine the pH of the egg album. The samples did not show bacterial growth of Salmonella sp. On the other hand, in relation to the investigation of E. coli, it was observed that eggs with albumin + glycerol coating, without coating + sprayed E. coli, with albumin coating + sprayed E. coli and albumin + glycerol + sprayed E. coli demonstrated bacterial growth at 0, 15, 30 and 30 days of storage, respectively. However, no formation of E. coli colonies was observed in uncoated or uncoated eggs, contaminated and subjected to ultraviolet light. It was found that the pH's of eggs coated with albumin + glycerol solution and albumin + glycerol + UV solution were lower at 7, 14, 21, 28 and 35 days, possibly due to the association of egg treatment with UV and protection of trained coatings. It is concluded that albumin and albumin + glycerol solutions promote protection of eggs against contamination by E. coli for 30 days of storage. The albumin + glycerol and albumin + glycerol + UV coatings delay the increase in albumin pH and, consequently, the loss of quality of eggs for consumption for 30 days of storage.